2018
DOI: 10.3390/nu10111665
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng (Panax ginseng Meyer) Oligopeptides Protect Against Binge Drinking-Induced Liver Damage through Inhibiting Oxidative Stress and Inflammation in Rats

Abstract: Panax ginseng C.A. Meyer (ginseng) is an edible and traditional medicinal herb, which is reported to have a wide range of biological activity and pharmaceutical properties. There were more studies on ginsenoside and polysaccharides, but fewer on ginseng oligopeptides (GOPs), which are small molecule oligopeptides extracted from ginseng. The present study was designed to investigate the effects and underlying mechanism of ginseng oligopeptide (GOPs) on binge drinking-induced alcohol damage in rats. Sprague Dawl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 49 publications
(107 reference statements)
4
38
0
Order By: Relevance
“…Generally, NF-κB interacts with inhibitor kappa B (IκB) to make it inactive in the cytoplasm under physiological conditions. When various stimuli lead it to return to phosphor-IκB, then IκB degrades, thereby translocating NF-kB to the nucleus and inducing the expression of its target genes, such as TNF-α and IL-1β [31,55,56]. The results demonstrated that the protein expression of NF-κB p65 (Figure 5b), Bax (Figure 5f), and caspase 3 (Figure 5g) were up-regulated, while the IκBα (Figure 5c) and Bcl 2 (Figure 5e) expression were down-regulated in rats in the ethanol group when compared with those of rats in the normal group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, NF-κB interacts with inhibitor kappa B (IκB) to make it inactive in the cytoplasm under physiological conditions. When various stimuli lead it to return to phosphor-IκB, then IκB degrades, thereby translocating NF-kB to the nucleus and inducing the expression of its target genes, such as TNF-α and IL-1β [31,55,56]. The results demonstrated that the protein expression of NF-κB p65 (Figure 5b), Bax (Figure 5f), and caspase 3 (Figure 5g) were up-regulated, while the IκBα (Figure 5c) and Bcl 2 (Figure 5e) expression were down-regulated in rats in the ethanol group when compared with those of rats in the normal group.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Bax, caspase-3, Bcl-2, HSP70, NF-κB (p65), and IκBα proteins in gastric tissue of experiment rats was determined by Western blot analysis according to the previously described procedures with some optimizing modifications [31,32]. In brief, total proteins were extracted from homogenates using RIPA lysis buffer and the concentration was determined according to the BCA method.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…When 4 g/kg of ethanol was administered in the preliminary test, ALD was not satisfactorily induced. Thus, we increased the concentration of ethanol to 7 g/kg in this experiment based on other previous studies [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…3 A). 65 , 66 , 67 , 68 , 69 , 70 , 71 Allicin, the compound found in fresh garlic blends, improves alcohol dehydrogenase activity in AFLD mice. Most of the Chinese herbs that exhibit an attenuation effect on AFLD act as anti-oxidative or anti-inflammatory agents.…”
Section: Chinese Herbs and Fatty Liver Diseasementioning
confidence: 99%